FTIR microspectroscopy of stained cells and tissues. Application in cancer diagnosis. Issue 1 (2010) - Pijanka, Jacek K.; Stone, Nicholas; Cinque, Gianfelice; Yang, Ying; Kohler, Achim; Wehbe, Katia; Frogley, Mark; Parkes, Gary; Parkes, Joanne; Dumas, Paul; Sandt, Christophe; Pittius, Daniel G. van; et al.
Abstract : It is widely accepted that FTIR spectroscopy has a huge potential in cancer diagnosis. However further work is required to bring this technique into pathology departments. One of the areas where big efforts will be required is the development of cell spectra databases to be used in the diagnosis of cancer. Presently, unstained cytology and tissue samples are studied with FTIR spectroscopy. However, it is not always possible to identify in unstained samples the types of cells present. In order to achieve this, samples need staining after FTIR spectra have been obtained. We have recently shown it is possible to obtain FTIR spectra of stained cells using a synchrotron source (10.1038/ labinvest .2010.8). This allows recording FTIR spectra from cells already characterized by pathologists. In order to further this work, we have now obtained FTIR spectra from stained (Papanicolau or Haematoxylin & Eosin) single cells using a benchtop spectrometer. This would be the logical step towards a clinical application in cancer diagnosis. The data here presented show that staining caused a decreased intensity of the peaks at 2920 cm −1 and 2850 cm −1, and the appearance of stronger peaks at 1374 cm −1 and 1040 cm −1 . The clinical applications are discussed.